Transformasi Digital: Optimalisasi Simdik dalam Peningkatan Mutu Pendidikan di SPM Muadalah Ulya - Muhammad Hunim; Aimah, Siti (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This article discusses the implementation of an Educational Management Information System (EMIS) in improving the quality of education at SPM Muadalah Ulya Darussalam - Blokagung, Banyuwangi. The Educational Management Information System, known in English as the Management Information System (MIS), is a control over business that includes the empowerment of people, files, technology, and procedures by management accounting to solve business problems. In the field of education, the Educational Management Information System (EMIS) is very necessary as Indonesia has entered the era of the industrial revolution 4.0, thus requiring the management of school information related to payments, activity status, attendance, and new student admissions. There are several supporting and inhibiting factors in the implementation of EMIS at SPM Ulya, including the availability of information system facilities and challenges in human resources as well as technical errors.